DO MOMENTUM STRATEGIES PERFORM BETTER FOR ISLAMIC STOCKS THAN FOR CONVENTIONAL STOCKS ACROSS MARKET STATES? - Tee, Lain-Tze; Kew, Si-Roei; Low, Soo-Wah (Economic Annals, 2019)
This study compares the mo-mentum profitability of Islamic and con-ventional stocks in Malaysia and examines whether the presence of momentum profits is market-state dependent. Winner portfolios are shown to outperform loser portfolios, sug-gesting that a momentum effect exists in the equity market. Islamic stocks exhibit stronger momentum than conventional stocks. Inter-estingly, although pursuing profit is not the primary goal of Islamic stock investors, the findings indicate that momentum profits for all Islamic stock trading strategies are higher than those for conventional stocks. The prof-its from momentum strategies for both stocks are market-state dependent. In all trading strategies, while there are significant positive momentum profits following market upturns, there is no evidence of profits subsequent to market downturns. Overall, Islamic stocks yield higher momentum profits than conven-tional stocks across market states. These find-ings are robust to using various measures of the state of the market. While the presence of momentum profits is also robust to the inclu-sion of Fama-French’s (1993) risk factors, the risk factors are unable to explain momentum profits, suggesting that the risk-adjusted mo-mentum profits are not due to risk compen-sation. Rather, the profitability is evidence of stock mispricing.